2019
DOI: 10.1534/genetics.119.302077
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the Nature of Missing Heritability in Human Traits Using Data from the GWAS Catalog

Abstract: Thousands of genes responsible for many diseases and other common traits in humans have been detected by Genome Wide Association Studies (GWAS) in the last decade. However, candidate causal variants found so far usually explain only a small fraction of the heritability estimated by family data. The most common explanation for this observation is that the missing heritability corresponds to variants, either rare or common, with very small effect, which pass undetected due to a lack of statistical power. We carr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 78 publications
1
46
0
Order By: Relevance
“…Case sample sizes of ∼10 2 are well powered only to identify common (MAF ~ 10%) variants with very strong effects (effect size β ~ 1), whereas sample sizes of 10 4 are required to identify MAF ~ 10% variants with weaker effects ( β ~ 0.1) ( 32 ). This explains why GWAS often employ cohort sizes of ~10 4 –10 6 , and why when studies increase their cohort sizes they tend to discover larger numbers of lower-effect loci ( 35 ).…”
Section: Genome-wide Association Studymentioning
confidence: 99%
“…Case sample sizes of ∼10 2 are well powered only to identify common (MAF ~ 10%) variants with very strong effects (effect size β ~ 1), whereas sample sizes of 10 4 are required to identify MAF ~ 10% variants with weaker effects ( β ~ 0.1) ( 32 ). This explains why GWAS often employ cohort sizes of ~10 4 –10 6 , and why when studies increase their cohort sizes they tend to discover larger numbers of lower-effect loci ( 35 ).…”
Section: Genome-wide Association Studymentioning
confidence: 99%
“…Other than polygenic contributions to complex traits and complex genetic interactions (such as epistasis), several additional phenomena have been proposed as potential underlying causes of the missing heritability including intrinsic GWAS experimental limitations, heritability overestimations, variants with small effect-size, epigenetic mechanisms, gene/environment interaction and acquired inheritance, and many others (Lopez-Cortegano and Caballero 2019 ; Trerotola et al 2015 ; Young 2019 ).…”
Section: Genome-wide Association Studies and The Missing Heritabilitymentioning
confidence: 99%
“…Thanks to strong collaborations, many large-scale genome-wide association studies (GWAS) have successfully identified many genetic determinants described to explain part of the pathophysiological mechanism underlying a wide range of traits. Despite these efforts and increased sample sizes, the explained variability of many traits is relatively small and only a small proportion of the familial heritability can be explained by the candidate variants found (Evangelou et al, 2018;López-Cortegano & Caballero, 2019;Manolio et al, 2009).…”
Section: Introductionmentioning
confidence: 99%